Longitudinal associations of radiation risk perceptions and mental health among non-evacuee residents of Fukushima prefecture seven years after the nuclear power plant disaster - Maiko Fukasawa; Norito Kawakami; Maki Umeda; Tsuyoshi Akiyama; Naoko Horikoshi; Seiji Yasumura; Hirooki Yabe; Yuriko Suzuki; Evelyn J. Bromet (Elsevier, 2020)
We aimed to explore the effects of prolonged radiation risk perceptions on mental health after the Fukushima nuclear power plant accident occurred in 2011. We investigated the longitudinal associations of radiation risk perceptions five years after the accident with psychological distress and posttraumatic stress symptoms two years later among non-evacuee community residents of Fukushima prefecture. A two-wave questionnaire survey was administered for 4,900 randomly sampled residents in 49 municipalities of Fukushima prefecture excluding the evacuation area designated by the Japanese government. Radiation risk perceptions were assessed with a seven-item scale. Psychological distress and posttraumatic stress symptoms were measured by the K6 and the six-item abbreviated version of the Posttraumatic Stress Disorder Checklist-Specific version, respectively. We investigated the associations of radiation risk perceptions in the first survey conducted in 2016 with psychological distress and posttraumatic stress symptoms in the follow-up survey conducted in 2017-18, controlling for the baseline level of distress or symptoms using multivariate logistic regression analyses. Valid responses were obtained from 1,148 residents (23.4%). Higher risk perceptions of radiation exposure in the first survey predicted later posttraumatic stress symptoms but not psychological distress after controlling for baseline symptoms or distress. High risk perceptions of radiation exposure after nuclear power plant accidents can lead to posttraumatic stress symptoms.